ChemInform Abstract: Microscopic Studies of Nonlocal Spin Dynamics and Spin Transport (Invited). Issue 27 (18th June 2015) - Adur, Rohan; Du, Chunhui; Cardellino, Jeremy; Scozzaro, Nicolas; Wolfe, Christopher S.; Wang, Hailong; Herman, Michael; Bhallamudi, Vidya P.; Pelekhov, Denis V.; Yang, Fengyuan; et al.
Abstract Review: 25 refs.